Application of SAK EMKM to MSME Business Actors - Alrasyid, Harun; Haliah, Haliah; Kusumawati, Andi (International Journal of Sustainable Applied Sciences, 2023)
Micro, small and medium enterprises in the city of Palopo are still constrained by the application of financial accounting standards for micro, small and medium entities. If left unchecked, it will complicate the preparation   of financial reports. This study aims to identify and analyze the factors that influence the application of SAK EMKM to MSME business actors in Palopo City. The population and sample for this study were 90 micro, small and medium business actors who met the sample criteria. This type of research data uses primary data in the form of a questionnaire.  Data analysis uses multiple linear regression analysis using Statistical Packages for Social Science (SPSS). The results of the study show that socialization, education level, perceptions and understanding of accounting have a significant and significant effect on the application of SAK EMKM.